Picking cotton [compact disc, unabridged] : our memoir of injustice and redemption - Thompson-Cannino, Jennifer (Tantor Audio, 2009)
In July of 1984 in Burlington, North Carolina, Jennifer Thompson was raped in her own bed by an armed assailant. Not two months later, Thompson identified Ronald Cotton as the attacker, who was tried and sentenced to life in prison. However, after eleven years behind bars, Cotton was found innocent through DNA testing. Some time later, the two met and forged an unlikely friendship.